FAKTOR-FAKTOR YANG MEMPENGARUHI EFEKTIVITAS AUDIT INTERNAL (Survei pada Perwakilan BPKP Provinsi Jawa Tengah) - Afrilia Rahmayanti; Dwi Cahyo Utomo (Diponegoro Journal of Accounting, 2019)
This research is a quantitative research that examines the effectiveness of internal audits in public sector organizations. The focus of this study is to examine factors that can affect the effectiveness of internal audit activities that have been carried out by the Representative Office of the Financial and Development Supervisory Agency of Central Java Province. These factors include the competence of internal auditors, the relationship between internal auditors and external auditors, management support, and the independence of internal auditors. The data of this study were obtained from 50 internal auditors who worked at BPKP Central Java through distributing questionnaires. Multiple regression analysis with the help of SPSS is used to examine all factors in affecting the effectiveness of internal auditors. The results of the study show that all the tested factors, namely the competence of internal auditors, the relationship between internal auditors and external auditors, support of management, and the independence of internal auditors have a significantly positive effect on the effectiveness of internal auditors.